Exercise echocardiography predicts development of left ventricular dysfunction in medically and surgically treated patients with asymptomatic severe aortic regurgitation. Issue 6 (1st December 2000) - Wahi, S; Haluska, B; Pasquet, A; Case, C; Rimmerman, C M; Marwick, T H
Abstract : OBJECTIVE: To assess resting and exercise echocardiography for prediction of left ventricular dysfunction in patients with significant asymptomatic aortic regurgitation. DESIGN: Cohort study of patients with aortic regurgitation. SETTING: Tertiary referral centre specialising in valvar surgery. PATIENTS: 61 patients (38 men, 23 women; mean (SD) age 53 (14) years) with asymptomatic or minimally symptomatic aortic regurgitation and no known coronary artery disease; 35 were treated medically and 26 had aortic valve replacement. INTERVENTIONS: Exercise echocardiography was used to evaluate ejection fraction, which was measured on the resting and post-stress images using the modified Simpson method. Patients with an increment of ejection fraction after exercise were denoted as having contractile reserve (CR+); those without an increment were labelled CR−. MAIN OUTCOME MEASURES: Standard univariate and multivariate methods and receiver operating characteristic analyses were used to assess the ability of contractile reserve to predict follow up ejection fraction. RESULTS: In the 35 medically treated patients, 13 of 21 (62%) with CR+ (mean (SD) ejection fraction increment 7 (3)%) had preserved ejection fraction on follow up. In the 14 patients with CR− (ejection fraction decrement 8 (4)%), 13 (93%) had a decrement of ejection fraction on follow up from 60 (5)% at baseline to 54 (3)% on follow up (p = 0.005). Age, resting left ventricular dimensions, medical treatment, aortic regurgitation severity, exercise capacity, and rate–pressure product were similar in both CR+ and CR− groups. Among the 26 surgical patients, 13 showed CR+ (ejection fraction increase 9 (5)%), all of whom had an increase in ejection fraction on follow up (from 49% to 59%). Of 13 surgical patients with CR− (ejection fraction decrease 7 (5)%), 10 (77%) showed the same or worse ejection fraction on postoperative follow up. CONCLUSIONS: Contractile reserve on exercise echocardiography is a better predictor of left ventricular decompensation than resting indices in asymptomatic patients with aortic regurgitation. In patients undergoing aortic valve replacement, contractile reserve had a better correlation with resting ejection fraction on postoperative follow up. Measurement of contractile reserve may be useful to monitor the early development of myocardial dysfunction in asymptomatic patients with aortic regurgitation, and may help to optimise the timing of surgery.